Effects of Nonthermal Plasma on Wheat Grains and Products - V. Scholtz; B. Šerá; J. Khun; M. Šerý; J. Julák (Journal of Food Quality)
This paper presents the review of effects of nonthermal plasma (NTP) treatment on both the wheat grains and flour with potential to be applied in practice. The NTP can be used in wheat grain surface disinfection, grain germination and vitality improving, and wheat flour modification and disinfection. NTP causes effective decontamination from bacteria and fungi together with insect pests and causes minimal damage to wheat grains; it inactivates enzymes and enhances the grain shelf life; it enhances the germination and initial state of growth resulting in the increase of final yield. Moreover, the production of qualitatively better dough is also mentioned.